Systematic revision of the genus Phaeaphodius Reitter, 1892 (Coleoptera: Scarabaeidae: Aphodiinae) - Dellacasa, Marco; Dellacasa, Giovanni (Zootaxa, 2016)
The genus Phaeaphodius Reitter, 1892 (Coleoptera: Scarabaeidae: Aphodiinae) is revised and considered to consist of 12 species. A key to species and diagnosis of each species are given to fascilitate identification. Lectotypes are designated for A. costalis Gebler, 1848, A. sibiricus Harold, 1863, A. aeger Sharp, 1878, and A. solskyi Harold, 1871. Neotypes are designated for A. alleoni d’Orbigny, 1896, A. fusculus Reitter, 1892, and A. trucantangulus Reitter, 1894. The name Aphodius fusculus Reitter, 1892 is placed in synonymy with Esymus pusillus (Herbst, 1789) (new synonymy).